Early retirement and post retirement health - Daniel Hallberg; Per Johansson; Malin Josephson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
This paper studies empirically the consequences of retirement on health. We make use of a targeted retirement offer to army employees 55 years of age or older. Before the offer was implemented in the Swedish defense, the normal retirement age was 60 years of age. Estimating the effect of the offer on individuals' health within the age range 56-70, we find support for a reduction in both mortality and in inpatient care as a consequence of the early retirement offer. Increasing the mandatory retirement age may thus not only have positive government income effects but also negative effects on increasing government health care expenditures.
Keywords: J22; J26; I18; 330; health; mortality; inpatient care; retirement; health care; pensions; occupational pensions